การปรับปรุงประสิทธิภาพคลังสินค้า ตามระเบียบวิธี DMAIC: Efficiency Improvement in the Inventory Based on DMAIC Methodology - Sinthavalai, Runchana; Touwato, Toha; Hayeeteh, Alfahud (Asian Health, Science and Technology Reports, 2018)
การวิจัยเพื่อเพิ่มประสิทธิภาพคลังสินค้าสำเร็จรูปของบริษัทกรณีศึกษานี้ ดำเนินการตามแนวทาง DMAIC ในระบบคุณภาพซิกส์ซิกมา การวิจัยเริ่มจากการกำหนดหัวข้อ (define stage) ซึ่งรับโจทย์ปัญหาจากทางบริษัทและศึกษาเชิงลึก พบว่าการส่งมอบสินค้าให้กับลูกค้าไม่เป็นไปตามเป้าหมายของบริษัทในด้านเวลา งานวิจัยจึงตั้งเป้าหมายเพื่อปรับปรุงให้การส่งมอบเป็นไปตามเป้าหมายมากขึ้น จากนั้นจึงเก็บข้อมูลสถานการณ์และตัวแปรต่างๆ (measure stage) เพื่อวิเคราะห์สาเหตุของปัญหา (analyze stage) ซึ่งจากการวิเคราะห์ด้วยผังก้างปลาและประเมินสาเหตุจากพนักงานร่วมกับผู้วิจัยพบ 2 สาเหตุหลักที่นำมาแก้ไข ได้แก่ สินค้าที่นิยมอยู่ไกลจากจุดส่งมอบ และตัวชี้วัดที่ทางบริษัทกำหนดไม่เหมาะสมในการทำงานจริง จากนั้นจึงร่วมกันกำหนดแนวทางแก้ไข (improve stage) ได้เป็น 2 ประเด็นหลักคือ (1) การปรับผังพื้นที่คลังสินค้า โดยได้นำเสนอ 3 แนวทางได้แก่ แนวทางตามเทคนิค Pair-Wise พบว่าสามารถลดระยะทางการเคลื่อนที่ลง 4,108 เมตรต่อวัน แต่เนื่องจากทางบริษัทต้องการให้มีผลกระทบจากการปรับผังน้อยที่สุด จึงนำเสนอแนวทางถัดมาคือการสลับเพียงคู่เดียวสำหรับพื้นที่เก็บสินค้าที่มีความต้องการซื้อสูงกับความต้องการซื้อไม่มากนัก เพื่อให้สินค้าที่มีความต้องการซื้อสูงอยู่ใกล้จุดส่งมอบ พบว่าสามารถลดการเคลื่อนที่ต่อวันลงได้ 1,517 เมตร และแนวทางสุดท้ายคือการย้ายจุดส่งมอบไปอยู่ใกล้กับพื้นที่เก็บสินค้าที่มีความต้องการซื้อสูง จะสามารถลดระยะทางการเคลื่อนที่ลงได้ 3,970 เมตรต่อวัน (2) การปรับตัวชี้วัดของคลังสินค้าเป็นสองกรณีเพื่อสะท้อนการทำงานจริงได้ชัดเจนกว่า ส่งผลต่อขวัญและกำลังใจของพนักงาน และความเข้าใจที่ถูกต้องของลูกค้ามากขึ้น กล่าวคือ กรณีสินค้าในใบสั่งซื้อไม่เกิน 10 รายการ กำหนดเวลาส่งมอบไม่เกิน 15 นาที และกรณีสินค้าในใบสั่งซื้อมากกว่า 10 รายการ กำหนดเวลาในการส่งมอบไม่เกิน 20 นาที โดยทั้งสองกรณีตั้งเป้าหมายความพึงพอใจที่ร้อยละ 75 ของใบสั่งซื้อทั้งหมด ในขั้นตอนการควบคุม (control stage) ทางผู้วิจัยได้ศึกษาผลกระทบที่อาจเกิดจากแนวทางการปรับปรุงต่างๆ เพื่อให้ทางบริษัทเตรียมการก่อนนำแนวทางไปใช้จริง This study was the improvement in the inventory efficiency. The study was based on DMAIC, which is key methodology in Six Sigma quality system. In the define stage, the problem was stated from the case study company. It found that this company has faced an inventory management problem making a customer service unable to achieve its goal. Therefore, the objective of this research is to improve the delivery process in order to meet the organization’s goal. Data collected was done in the measure stage, in order to understand the situation and relevant data. In the analyze stage, root causes were analyzed by a fishbone diagram. Two main causes were chosen to be solved; the popular products located far away from a product delivery point, and the unsuitable key performance indicator. Subsequently, in the improve stage, two solutions were proposed. The first solution was to modify an inventory space. For this method, 3 ways which could reduce the distance of delivery was criticized. Pair-Wise technique was the first one. By this approach, the distance of delivery could be reduced for 4,108 meters per day. However, the company needed to modify a system scheme having the slightest effect on the old scheme. Therefore, another two ways were employed. Firstly, switching only two areas was stated. It was the aim to move the popular product close to a product delivery point. This can reduce 1,517 meters per day. Secondly, if the position of a product delivered was moved to be close to the area for storing the popular product, the movement could be reduced for 3,970 meters per day. The second solution was to adjust the key performance indicator. The indicator should be classified into 2 situations. For the purchase order with fewer than 10 items, the delivery was not over 15 minutes. For the purchase order with more than 10 items, the delivery was not over 20 minutes. Both situations were targeted at a 75 percent overall the whole purchase order. In the control stage, the possible effects when implementing these solutions were analyzed prior to set up the countermeasures.